Ochre fingerprints: Distinguishing among Malawian mineral pigment sources with Homogenized Ochre Chip LA–ICPMS. (12th March 2014) - Zipkin, A. M.; Hanchar, J. M.; Brooks, A. S.; Grabowski, M. W.; Thompson, J. C.; Gomani‐Chindebvu, E.
Abstract : In this study, we compared the effectiveness of instrumental neutron activation analysis (INAA) of bulk ochre to laser ablation‐inductively coupled plasma mass spectrometry of homogenized ochre chips (HOC LA–ICPMS) at distinguishing among three ochre sources in northern Malawi. Both techniques upheld the Provenance Postulate; however, HOC LA–ICPMS required less sample material than INAA and facilitated fast, inexpensive replicate observations that allowed for more robust statistical analysis. Our results indicated that HOC LA–ICPMS is a maturing technique that will be a valuable option for analysing artefacts that require minimally destructive sampling but are too large to fit into the laser cell for direct ablation. With regard to the statistical procedures used, stepwise canonical discriminant analysis was demonstrated to be a highly effective method for distinguishing among ochre sources, even in the presence of significant intra‐source and intra‐sample heterogeneity. Continued development of the HOC sample preparation technique will expand the range of archaeological ochre artefacts that can be included in provenance studies and prevent bias towards artefacts of convenient‐to‐analyse dimensions.